Mental health of postgraduate trainees in primary care: a cross-sectional study - Bugaj, Till Johannes; Krug, Katja; Rentschler, Annalena; Nikendei, Christoph; Szecsenyi, Joachim; Schwill, Simon (BMC family practice, 2020)
General Practitioners (GPs) are increasingly affected by stress-related complaints and burnout. Although many studies have addressed this issue, little is known about the stress burden and burnout rates of postgraduate trainees specialising in General Practice (GP). This cross-sectional study was performed to explore the prevalence and risk of depression, stress and burnout in a large cohort of GP trainees.
Gesehen am 27.07.2020